1979
DOI: 10.1073/pnas.76.12.6646
|View full text |Cite
|
Sign up to set email alerts
|

Immunofluorescent localization of angiotensin converting enzyme in epithelioid and giant cells of sarcoidosis granulomas.

Abstract: Angiotensin converting enzyme (ACE) (dipeptidyl carboxypeptidase; peptidyldipeptide hydrolase, EC 3.4.15.1) was localized in epithelioid and giant cells within ACE-rich sarcoidosis granulomas, but not control granulomas, by immunofluorescence by using a rabbit anti-human ACE immunoglobulin for localization and fluorescein-labeled goat anti-rabbit immunoglobulin for detection. ACE was frequently not detected in the very central epithelioid cells, perhaps due to a paucity of cellular or molecular stimulatory int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
1
4

Year Published

1980
1980
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(65 citation statements)
references
References 21 publications
1
55
1
4
Order By: Relevance
“…Since the evidence has been brought that ACE is produced by epitheloid cells of sarcoid granulomas, and after the elevated serum ACE levels (sACE) were found in patients with sarcoidosis, sACE has been proposed to be the marker of sarcoidosis activity, susceptibility and prognosis (Pertschuk et al 1981;Lieberman 1975;Meeting Report 1994). It has also been demonstrated that ACE synthesis in a monocyte cell culture can be modulate by T lymphocytes obtained from sarcoid patients (Silverstein et al 1979). It is now believed that sACE reflects the whole body granuloma mass (Ainslie et Benatar 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Since the evidence has been brought that ACE is produced by epitheloid cells of sarcoid granulomas, and after the elevated serum ACE levels (sACE) were found in patients with sarcoidosis, sACE has been proposed to be the marker of sarcoidosis activity, susceptibility and prognosis (Pertschuk et al 1981;Lieberman 1975;Meeting Report 1994). It has also been demonstrated that ACE synthesis in a monocyte cell culture can be modulate by T lymphocytes obtained from sarcoid patients (Silverstein et al 1979). It is now believed that sACE reflects the whole body granuloma mass (Ainslie et Benatar 1985).…”
Section: Discussionmentioning
confidence: 99%
“…A decreased SACE level has also been found in malignant lymphoproliferative and haematological disorders in which SACE was also associated with prognosis, though not so regularly as observed in lung cancer (R0mer & Emmertsen, 1980). With regard to other lung diseases, measurement of SACE has been mostly used in sarcoidosis (Lancet, Editorial, 1980;R0mer, 1979), where high SACE is presumably due to increased formation in the monocyte macrophage-derived noncaseating epithelioid granulomas (Silverstein et al, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…The finding of a high ACE activity in sarcoid lymph nodes (Silverstein et al, 1976) and the demonstration of ACE in sarcoidosis epithelioid cells (Silverstein et al, 1979) point to the monocyte-macrophagederived epithelioid-cell granuloma as the source of high SACE in sarcoidosis.…”
mentioning
confidence: 96%